Recognising and certifying lifelong skills: impact on labour market integration of the unemployed - Fernandes, Pedro Afonso [Verfasser] (My University, 2010)
"The process for recognising, validating and certifying (RVC) non-formally or informally acquired lifelong learning, launched in 2000, is now part of mainstream education and training policies in Portugal. This article aims to determine how much the labour-market behavior of the RVC-certified unemployed differs from that of other unemployed persons, using an econometric estimate of conditional and unconditional models, supported by a purpose-built longitudinal database. A comparative analysis of the certified unemployed from 2001 to 2003 and those registered at job centres at the end of 2003 supports the hypothesis that RVC favours the transition between unemployment and employment, especially where (very) long-term unemployment is concerned. The role of RVC in encouraging the unemployed to transit to inactivity to undertake formal learning, however, is less clear." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Informelles Lernen; Anerkennung; Zertifizierung; Arbeitsmarkt; Berufliche Integration; Arbeitslosigkeit; Portugal